2016
DOI: 10.1055/s-0042-101412
|View full text |Cite
|
Sign up to set email alerts
|

Life-Long Wheel Running Attenuates Age-Related Fiber Loss in the Plantaris Muscle of Mice: a Pilot Study

Abstract: The purpose of this study was to investigate whether long-term wheel running would attenuate age-related loss of muscle fiber. Male ICR mice were divided into young (Y, n=12, aged 3 months), old-sedentary (OS, n=5, aged 24 months), and old-exercise (OE, n=6, aged 24 months) groups. The OE group started spontaneous wheel running at 3 months and continued until 24 months of age. Soleus and plantaris muscles were fixed in 4% paraformaldehyde buffer. The fixed muscle was digested in a 50% NaOH solution to isolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…Wild‐type mice ran significantly more than mtDNA mutator mice during the 30 weeks of training (1,302 ± 271.2 km vs. 570.9 ± 83.6 km) (Figure b and c). Running activity in both groups peaked between the 3rd and 9th week and then declined, as also seen in other studies (McMullan et al, ; Suwa et al, ; Figure c). Combining sexes, the WT mice ran more than mtDNA mutator mice during all 30 weeks.…”
Section: Resultssupporting
confidence: 89%
“…Wild‐type mice ran significantly more than mtDNA mutator mice during the 30 weeks of training (1,302 ± 271.2 km vs. 570.9 ± 83.6 km) (Figure b and c). Running activity in both groups peaked between the 3rd and 9th week and then declined, as also seen in other studies (McMullan et al, ; Suwa et al, ; Figure c). Combining sexes, the WT mice ran more than mtDNA mutator mice during all 30 weeks.…”
Section: Resultssupporting
confidence: 89%
“…Voluntary physical exercise was chosen instead of treadmill exercise as the voluntary paradigm has been shown to be more tolerable and induce lower stress levels, demonstrated by measurements of serum corticosterone [ 33 ]. In agreement with existing studies [ 34 , 35 ], we monitored the amount of exercise undertaken by the mice and discovered that the weekly running distance and time was 30 ± 1 km and 20 ± 1 h, respectively. The refinement of an appropriate exercise regime to effectively regulate the neuroinflammatory response in AD model mice may be of high relevance to the human population and should be considered in all studies using experimental animals.…”
Section: Discussionsupporting
confidence: 88%
“…With the caveat that this is a very rough indicator of fiber number that is affected also by changes in muscle architecture, this is in contrast to previous reports suggesting a similar contribution of fiber atrophy and fiber loss to the age-related atrophy in non-athletes, 1,4 but in line with a previous study showing no age-related loss of fibers. 38 In rat plantaris muscle, it has been reported that the aging-related loss of fibers is attenuated by intensive running exercise 39 and strength training. 40 The discrepancy may therefore be related to differences in physical activity patterns, with higher levels of physical activity of the non-sarcopenic participants 38 and our athletes than that of the recreationally active sarcopenic older people in our previous work.…”
Section: Muscle Fiber Cross-sectional Area (Fcsa)mentioning
confidence: 99%